Management of Brachial Plexus Birth Palsies: The Stanford Experience - Park, Eugene; Fox, Paige M.; Curtin, Catherine; Hentz, Vincent R. (Seminars in Plastic Surgery, 2023)
The start of Stanford's brachial plexus birth palsy (BPBP) experience dates back to 1983, when Dr. Vincent Rod Hentz visited Dr. Alain Gilbert on sabbatical. Since then, our principles of care for patients with BPBP have evolved based on our group's longitudinal experience caring for children with the entire spectrum of sequelae that arise in children with BPBP. We base our clinical decision making on frequent serial examinations and use intraoperative evoked potentials to guide surgical decisions. Here, we discuss our current principles on surgical indications, timing of surgery, and preferred techniques for secondary surgery in patients with BPBP.
Keywords: birth brachial plexus palsy; nerve grafting; nerve transfers; reconstructive strategy